Serum angiotensin-converting enzyme in malignant lymphomas, leukaemia and multiple myeloma. - Rømer, F. K. (Nature Publishing Group, 1980)
Serum angiotensin-converting enzyme (SACE) was analysed in 27 patients with Hodgkin's disease, 25 with non-Hodgkin lymphoma, 14 with acute leukaemia, 15 with chronic leukaemia, and 15 with multiple myeloma. SACE was depressed in these patients as a whole, with a mean level of 19.9 mu/ml, compared with 116 healthy controls (mean 24.4 mu/ml, P < 0.001). This depression was greatest in chronic leukaemia and multiple myeloma. In Hodgkin's disease no relationship was found between enzyme activity and stage, activity, histopathology, treatment, mediastinal involvement or prognosis. In non-Hodgkin patients a poor prognosis was generally associated with low SACE activity. The low SACE activity was not related to recent corticosteroid treatment, and the cause and pathophysiological significance is unexplained. Since SACE is high in the granulomatous disorder sarcoidosis (which can mimic malignant lymphnode and blood diseases) SACE analysis can be valuable in evaluating patients with mediastinal lymphadenopathy and those in whom non-caseating epitheliod granulomas are found.